Surface modification of an AISI 1045 steel by a nitriding and post-oxidation duplex process in pulsed DC plasma (Superficies y Vacío, 2012)
The Present work shows a study on the effect of “Pulsed Plasma Nitriding and Post-Oxidation” treatment on mechanical properties and electrochemical corrosion performance (3% NaCl solutions) of a steel AISI 1045. The effect of temperature and processing time on surface hardness, oxidized layer thickness, electrochemical corrosion rate and crystalline phases was evaluated. Results show that post oxidation treatment at 400°C during 30 minutes promotes a reduction of corrosion rate about 50% the corrosion rate of the untreated reference sample. This phenomenon is attributed to the growing of a oxide thin film (about 400 nm thickness) constituted mainly of magnetite (Fe3O4) on a nitrided layer compose by Fe3N/Fe4N. Nitriding post oxidation process increases the hardness and corrosion performance of a common steel with several applications in industy.